2003
DOI: 10.1063/1.1523898
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen atom interactions with fused silica surfaces: 1D and 3P state-resolved energy transfer dynamics

Abstract: A laser-based O atom beam source together with state-resolved detection techniques are used to characterize the energy transfer dynamics of ground (3P) and electronically excited (1D) state O atoms interacting with a fused silica surface. Time-of-flight spectra of the incident beam and scattered O atoms are measured, and provide detailed information regarding state-resolved angular and velocity distributions. We find a significant degree of “thermalization” (angular, fine structure state, and velocity distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, oxygen radical-surface collisions are a component of oxygen plasma treatments that are used to enhance adhesion 6 and biocompatibility. 7 Similarly, as a result of the importance of silicon oxidation and the use of oxygen plasmas in semiconductor processing, studies of AO reactions with clean silicon, 8 fused silica, 9 and hydrocarbon terminated Si͑100͒ surfaces 10 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxygen radical-surface collisions are a component of oxygen plasma treatments that are used to enhance adhesion 6 and biocompatibility. 7 Similarly, as a result of the importance of silicon oxidation and the use of oxygen plasmas in semiconductor processing, studies of AO reactions with clean silicon, 8 fused silica, 9 and hydrocarbon terminated Si͑100͒ surfaces 10 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum-ultraviolet (VUV) light ( h ν ≳ 6.2 eV) efficiently decomposes interstitial O 2 in a -SiO 2 and generates interstitial O 0 . , Theoretical studies have shown that an interstitial O 0 in a -SiO 2 is readily incorporated into the Si–O–Si network to form a peroxy linkage (POL, Si–O–O–Si). The presence of mobile O 0 in a -SiO 2 is indicated by the creation of interstitial O 2 through the radiolytic decomposition of regular Si–O–Si bonds (Frenkel process), , the formation of interstitial ozone molecules (O 3 ), and the interconversion between oxygen dangling bonds (nonbridging oxygen hole center, NBOHC, SiO • ) and peroxy radicals (POR, SiOO • ) . Interactions between O 0 and the surfaces of a -SiO 2 have attracted attention because of their relevance for plasma processing and catalysis . However, isotope labeling, which is a powerful tool for investigating diffusion and reactions of chemical species, has not been used to study interstitial O 0 in a -SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…5−11 The presence of mobile O 0 in a-SiO 2 is indicated by the creation of interstitial O 2 through the radiolytic decomposition of regular Si−O−Si bonds (Frenkel process), 5−7,12−17 the formation of interstitial ozone molecules (O 3 ), 18 and the interconversion between oxygen dangling bonds (nonbridging oxygen hole center, NBOHC, SiO • ) and peroxy radicals (POR, SiOO • ). 19 Interactions between O 0 and the surfaces of a-SiO 2 have attracted attention because of their relevance for plasma processing 20 and catalysis. 21 However, isotope labeling, which is a powerful tool for investigating diffusion and reactions of chemical species, has not been used to study interstitial O 0 in a-SiO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%